2014
DOI: 10.1002/tea.21163
|View full text |Cite
|
Sign up to set email alerts
|

Replicating Peer‐Led Team Learning in cyberspace: Research, opportunities, and challenges

Abstract: This quasi-experimental, mixed methods study examined the transfer of a well-established pedagogical strategy, Peer-Led Team Learning (PLTL), to an online workshop environment (cPLTL) in a general chemistry course at a research university in the Midwest. The null hypothesis guiding the study was that no substantive differences would emerge between the two workshop settings. Students in the PLTL (n ¼ 220) condition were more satisfied with their workshop and earned statistically significantly higher course grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 70 publications
(78 reference statements)
2
42
0
Order By: Relevance
“…Screencasts themselves could be more interactive, or be user-dependent, so that students could explore their understanding (e.g. Discussion fora have been described for chemistry to enable peer interactions (Seery, 2012a(Seery, , 2012bSmith et al, 2014). Students with identified misconceptions based on their response could be diverted through some activities that would assist their comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Screencasts themselves could be more interactive, or be user-dependent, so that students could explore their understanding (e.g. Discussion fora have been described for chemistry to enable peer interactions (Seery, 2012a(Seery, , 2012bSmith et al, 2014). Students with identified misconceptions based on their response could be diverted through some activities that would assist their comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…organic chemistry to reduce high student attrition rates, enhance student motivation and engagement, and increase achievement in chemistry (Gosser & Roth, 1998;Hockings, De Angelis, & Frey, 2008;Kampmeier & Varma-Nelson, 2009;Lewis, 2011;Lewis & Lewis, 2005Mitchell et al, 2012;Shields et al, 2012;Smith et al, 2014;Tien et al, 2002;Varma-Nelson & Coppola, 2005;Wamser, 2006).…”
mentioning
confidence: 99%
“…cPLTL employs software designed for online collaboration to facilitate interactions from student to student and student to peer leader. Research has found mostly positive but somewhat mixed findings from early adoption of cPLTL (18). First, the gains in student performance and limiting withdrawals with cPLTL were comparable to that observed with the conventional in-person PLTL.…”
Section: Cyber Peer-led Team Learningmentioning
confidence: 71%
“…Cyber Peer-Led Team Learning (cPLTL) has been recently developed to incorporate PLTL into an online learning experience (18). Like the use of flipped classes, this also takes advantage of the rising ease in substantial communications in an online platform.…”
Section: Cyber Peer-led Team Learningmentioning
confidence: 99%